Ideologi Muhammadiyah - Fyroza Mustika Akhlis (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This article discusses the ideology of Muhammadiyah, the largest Islamic organization in Indonesia which was founded by KH. Ahmad Dahlan in 1912. Muhammadiyah ideology focuses on purifying Islamic teachings, with the aim of returning religious practices to the Koran and Sunnah of the Prophet. Throughout its journey, Muhammadiyah has also adopted a modern and progressive approach in the fields of education, health and social welfare. This article explores the basic principles of Muhammadiyah ideology, including the concepts of purification (tajdid) and renewal (islah), as well as their implementation in various social programs and activities. Apart from that, the challenges and adaptations of this ideology in facing social, political and cultural dynamics in Indonesia are also discussed. Through this analysis, this article aims to provide a comprehensive understanding of the contribution and relevance of Muhammadiyah ideology in the context of modern society.